Faktor-faktor yang berhubungan dengan turnover intention perawat di ruang rawat inap di Rumah Sakit TK III Dr. Reksodiwiryo Padang Tahun 2024 - Putri, Febri Nur Azizah; Sari, Rebbi Permata; Rasyid, Willady (STIKes Alifah Padang, 2024)
Nurse turnover intention refers to a nurse's intent to voluntarily leave their job. Several factors influence nurse turnover intention, including job satisfaction, job stress, and organizational culture. This study aimed to determine the factors associated with nurse turnover intention in Inpatient Wards at Dr. Reksodiwiryo Level III Hospital, Padang, in 2024. This was a quantitative cross-sectional study. The population comprised 115 nurses in Inpatient Wards at Dr. Reksodiwiryo Level III Hospital, Padang. Data were collected from May 6 to 11, 2024, using a purposive sampling technique involving 53 respondents through the distribution of questionnaires. Data were analyzed univariately and bivariately using the Chi-Square test with a p-value ≤ 0.05.The results showed that more than half (59.8%) of the nurses had a high turnover intention, less than half (32.1%) were dissatisfied with their job, less than half (41.5%) experienced high job stress, and more than half (56.6%) perceived the organizational culture as poor. This study indicated that there was a relationship between job satisfaction (p-value 0.035), job stress (p-value 0.030), and organizational culture (p-value 0.016) with nurse turnover intention in Inpatient Wards at Dr. Reksodiwiryo Level III Hospital, Padang in 2024. The conclusion of this study is that there is a relationship between job satisfaction, job stress, and organizational culture with nurse turnover intention in Inpatient Wards at Dr. Reksodiwiryo Level III Hospital, Padang in 2024. It is recommended that the head nurse of the medical-surgical units implement a career development program, stress management training, and improve the organizational culture.